Drinking water quality evaluation of hand pumping wells using water quality index and standard algal toxicity testing in Mansoura and Talkha cities, Egypt (Baghdad Science Journal, 2021)
Six house-hold Abyssinian pumps distributed in different villages of Mansoura (Mans-I, Mans-II and Mans-III) and Talkha (Talk-I, Talk-II and Talk-III) cities, Egypt, have been selected for regular seasonal water quality assessment during 2017. Water samples have been collected within the mid-periods of four seasons Standard assessment tools were employed for the integrated water quality assessment including Water Quality Index (WQI) and ISO standard algal toxicity test. WQI displayed remarkable local and seasonal variations with excellent (≥ 90) and good (70 - 89) only recorded for water samples collected from Mans-I pump located in sparsely populated area and far 50 meters only from the eastern (Damietta) branch of Nile River. WQI of other pumps located in densely populated areas and far kilometers from the Nile branch indicated either medium (50-69) or bad (25-49) quality depending on sampling season and sampling site location. All water samples collected from the pump Mans-I were non toxic without any inhibitory effects on the growth of the standard test alga Pseudokirchneriella subcapitata. Water samples from all other pumps, however, showed obvious toxic effects on test algae growth with varying EC50 values ranged between15.8% and 83%, depending on water sample and the sampling season. Concisely, all water samples collected from Mans-I pump were health safe with acceptable drinking water guidelines while samples collected from other pumps can impose great human health risks if used for drinking